Analisis Efektivitas Program Penyaluran Dana Zakat untuk Beasiswa Bagi Siswa/Mahasiswa Muslim yang Kurang Mampu pada Baznas Kota Pematangsiantar - Anugrah Ramanda; Muhammad Syahbudi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This study aims to analyze the effectiveness of the zakat fund distribution program for scholarships for students or Muslim students or Muslim women who are less fortunate at BAZNAS Pematangsiantar City. This method uses a qualitative and quantitative approach. The results of this study show that the distribution of zakat funds for underprivileged students has been running effectively, according to several benchmarks of effectiveness. Even though there are still deficiencies in channeling zakat funds, the current method carried out by the BAZNAS of Pematangsiantar City is quite right on target for students in Pematangsiantar City. Keywords: Scholarship, Effective, and zakat